Phytochemistry, Pharmacological Actions and Market Formulations of Sea buckthorn (Hippophae rhamnoides L.): A Comprehensive Review - Prakash, Surya; h, Hurmat; Yadav, Sangita (Pharmacognosy Reviews)
Plants have been utilized for the treatment of various diseases since ages because of their plethora of pharmacological actions and almost inferior side effects. Among all medicinal plants seas buckthorn also came into limelight because of its unique appearance and valuable phytoconstituents as well as medicinal properties. The sea buckthorn known as Hippophae rhamnoides L. belonging to family Elaeagnaceae is a berries bearing plant. This review explores the plant profile, phytochemistry, pharmacological activities including: in vivo, in vitro, clinical studies of the plant and market preparation till date of sea buckthorn. The data was collected by comprehensively searching various scientific search engines i.e., PubMed, Google Scholar, web of science etc. According to literature plant contains various phenolic and non-phenolic secondary metabolites and nutrients. Majorly plants contains Carotenoids, Triterpenoids, Phenolic compounds i.e. Kaempferol, quercetin, gallic acid, Catechin, Epicatechin, Gallo catechin etc. Apart from these different parts of the plants also contains Lipids, Proteins, fatty acids, sterols; volatile compounds, Amino acids, Proteins, Sugars, Pectin, Vitamins (C, E, B, K1, D, A, folic acid) Macro and trace elements (potassium, magnesium, calcium, iron, sodium, manganese, zinc, copper, nickel). Sea buckthorn is known for its antioxidant, anti-cancer, antidiabetic, hepatoprotective, wound healing, anti-bacterial, anti-viral etc. pharmacological properties. In conclusion, the elaborate tapestry of sea buckthorn’s phytochemistry and its multifaceted pharmacological actions has illuminated a promising path for both nutritional and therapeutic exploration. However, the paper's identification of substantial data gaps will spur more research and development, particularly for the creation of nutraceuticals and herbal medicines based on sea buckthorn.
Keywords: Sea buckthorn; Hippophae rhamnoides; Antioxidant; Anti-cancer; Phenolic compounds